Implementasi Model Pembelajaran Kooperatif Dengan Siklus ADE Berbasis Portofolio - Rahma Faelasofi; Suminto (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2020)
The purpose of this studywasto increase students’motivation and learning outcomes related to the implementation of cooperative learning models with a cycle of activity, discussion, and exercise based-portfolio. Classroom Action Research (CAR) was conducted in thethird semester students designed with two cycles, in whicheach cycle had plan, implementation, observation, and reflection. The collected data were dataabout students’learning motivation and students’learning outcomes. Then the data were analyzedbyusing descriptive statistics. Based on the results of data analysis in the first cycle,the average of students’ learning reached 58.55 and in the second cycle,the average of students’ learning motivation reached 82.91. While the average scoreof student learning outcomes obtained in the first cycle was 61.43 and in the second cycle was 79.29. Thus,it could be concluded that there was an increase in students’ learningmotivation andlearning outcomes through lectures by using cooperative learning model with ADE cycle of portofolio-based.